Proyecciones para la campana 1984/85 - Ospina Patiño, Bernardo (International Center for Tropical Agriculture, 1984)
The projections of the dried cassava project on the Colombian Atlantic Coast for 1984-85 are discussed. The installed capacity of the present cassava drying plants will be increased from 7180 square meters in June 1984 to 9100 square meters in 1985. Ten new plants will be established, based on an evaluation of selected criteria: 3 in Cordoba, 2 in Sucre, 1 in Bolivar, 2 in Atlantico, 1 in Magdalena, and 1 in Cesar. As of Dec. 1984, the installed capacity will be 14,000 square meters of drying floor, with a total production of 3500 t dry cassava/yr. (CIAT)